PENERAPAN METODE INKUIRI DALAM PEMBELAJARAN MENULIS PUISI SISWA SMK - Siti Alpiah; Wikanengsih Wikanengsih (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
Research problems are planning, implementation, and the results of the application of inquiry methods in learning to write poetry in vocational students. This research is based on the lack of poetry writing skills of vocational students. The study aims to describe how the application of the inquri method in the learning process of writing poetry of vocational students? The method of this research is descriptive method. The research technique is observation and testing. The research subjects were 32 students of Class X Marketing 2. The results of the study are 1) planning the implementation of the inquri method in learning is appropriate, 2) the implementation of the application of the inquri method during learning, carried out by the teacher according to the RPP arranged 3) the results of the application of inquiry methods in referral, the initial test average value 63.21 and the average value the final test is 80.91. There was an increase of 17.7%. In conclusion, the inquiry method is effectively applied in poetry writing skills.